2013
DOI: 10.1021/jp4097919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Group Charge on the Photooxidation Kinetics of Aromatic Amino Acids

Abstract: The kinetics of the photooxidation of aromatic amino acids histidine (His), tyrosine (Tyr), and tryptophan (Trp) by 3,3',4,4'-benzophenonetetracarboxylic acid (TCBP) has been investigated in aqueous solutions using time-resolved laser flash photolysis and time-resolved chemically induced dynamic nuclear polarization. The pH dependence of quenching rate constants is measured within a large pH range. The chemical reactivities of free His, Trp, and Tyr and of their acetylated derivatives, N-AcHis, N-AcTyr, and N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
(66 reference statements)
3
21
0
Order By: Relevance
“…49 Photoreduction of BP and its derivatives by the H-abstraction process has been studied in the presence of various hydrogen-containing substrates, including aliphatic hydrocarbons, alcohols and ethers, [50][51][52][53] nucleic acids, 54-55 lipids 47 and amino acids. [56][57][58] These studies have been mainly conducted in non-aqueous media and the determined rate constants fall in the range 10 4 to 10 9 M -1 s -1 , while Porter has reported that protons can quench the phosphorescence of BP in aqueous solution with a rate constant of 6•10 8 M -1 s -1 . 59…”
Section: Near-infrared Lanthanide(iii) Emissionmentioning
confidence: 99%
“…49 Photoreduction of BP and its derivatives by the H-abstraction process has been studied in the presence of various hydrogen-containing substrates, including aliphatic hydrocarbons, alcohols and ethers, [50][51][52][53] nucleic acids, 54-55 lipids 47 and amino acids. [56][57][58] These studies have been mainly conducted in non-aqueous media and the determined rate constants fall in the range 10 4 to 10 9 M -1 s -1 , while Porter has reported that protons can quench the phosphorescence of BP in aqueous solution with a rate constant of 6•10 8 M -1 s -1 . 59…”
Section: Near-infrared Lanthanide(iii) Emissionmentioning
confidence: 99%
“…The pH dependent protonation states of reactive species together with the acidity constants employed in calculations are listed in Tables 2 and 1, correspondingly. The equilibrium concentrations of the protonation forms of TCBP were calculated using two mean ground-state acidity constants p K a1 = 2.9 and p K a2 = 4.9 for H 2 O, 13 and p K a1 *=2.7 and p K a2 *=4.8 for D 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…[74] Third, capabilities of CIDNP can be extended by designing novel pulse sequences aimed at polarization transfer to target nuclei of choice and at fast 2D-NMR detection. Fourth, progress can be achieved in designing efficient photo-sensitizers [53] with the aim to detect biomolecules at very low concentrations. Last but not least, to 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 probe the structure of short-lived radicals one can study not only 1 H-CIDNP, but also CIDNP of hetero-nuclei, such as 13 C or 15 N. Such studies can be done either by direct detection of polarization of hetero-nuclei [55a,56] or by polarization transfer to protons followed by 1 H-NMR detection [30a] .…”
Section: Discussionmentioning
confidence: 99%
“…As photosensitizers, which are used to initiate a photo‐reaction giving rise to CIDNP, various dyes are used, which are listed in Scheme . These dyes are 2,2‐dipyridyl (DP),– 4‐carboxy‐benzophenone (4‐CBP),,, 3,3′,4,4′‐tetracarboxybenzophenone (TCBP),, and flavins with different substituents (flavin mononucleotide, FMN, is shown in Scheme ) ,,,. For running experiments under special conditions, i. e., at very low concentrations, one can also use other dyes, such as fluorescein .…”
Section: Cidnp Of Amino Acids and Nucleotidesmentioning
confidence: 99%
See 1 more Smart Citation